Teacher intervention during mathematical problem solving - Chapman, Olive (1999)
A humanistic problem-solving inservice program is discussed in terms of its effect on how elementary teachers intervened during problem-solving instruction. The effect is discussed from the perspective of symbolic interaction, i.e., a focus on the teachers´ personal meaning and supporting symbolic systems. As a result of participating in the program, the teachers constructed a different set of symbolic systems to guide their interactions with students in a way that emphasised an autonomous role for the students during problem solving. The paper provides insights of teacher classroom behaviour in terms of such symbols that are important in understanding the teacher´s perspective of teaching problem solving and how to facilitate meaningful changes for the teacher.